Conducta maternal e influencia del nido sobre la mortalidad neonatal en cerdos en un sistema de producción - Salazar Prado, José Ricardo (2017)
The pigs are animals species well adapted for the production of meat to be animals that grow and mature quickly, have a short period of gestation and very prolific, however, is a species that has a neonatal mortality is very high compared with other species of domestic animals. The objective of the present work was to determine maternal behavior and the influence o on mortality of the pigs in the first week of life in a production system. The pilot phase developed in the farm pork "San Francisco" located in the parish Chacras, Canton Arenillas, El Oro Province. The method of experimental type, contemplated the study behavioral maternal of 10 females calved and their offspring during the first week postpartum grouped into 2 treatments: Treatment 1 (T1) included 5 females in normal conditions of upbringing in maternity and the Treatment 2 (T2) which included the introduction of a nest in the cage of motherhood of 5 females. The participating mothers were selected at random. The study behavioral and mortality of pups was continuous, i.e. type circadian during the first 7 days of life for both treatments. The results show that mothers pass the higher % of time circadian supine position, slightly higher for T1 (75,93%) that for T2 (67,15%) while the left decubitus position for breastfeeding was higher for mothers of T2 (21.05%) than for T1 (10,48%) influenced by the position of the nest while the greater tendency circadian to this position was observed in the early hours of the morning and the night. In relation to the surface of slat, calves showed a widespread tendency, in both treatments, to their permanence thrown in bunching, slightly higher for T2 (50,12%) possibly by possess nest in the cage and however not to be in the same; as advanced in age, the offspring with nest threw scattered in this. The evolution of body weight shows a lower average in the offspring of T2 at birth and during the first week of life while the evolution of the body temperature displays the opposite effect to be greater in the offspring T2. To analyze the variable mortality was observed that the number of deaths in childbirth was much higher in T2 but this situation is stopped, in principle by the effect nest and the improvement in the welfare conditions for these offspring were born with lower average live weight than those of T1. It is concluded that the presence of the nest established better conditions for the welfare of calves by allowing them to maintain a thermal stability of comfort that resulted in a good indicator of survival for the first week of life despite be products of litters affected by different reasons at birth.